What's heaven? - Shriver, Maria; Speidel, Sandra (New York : Golden Books, 1999)
After her great-grandmother's death, a young girl learns about heaven by asking her mother all kinds of questions.
Accelerated Reader AR
Keywords: Heaven -- Fiction; Death -- Fiction; Great-grandmothers -- Fiction